CCL23 is a potential biomarker for antineutrophil cytoplasmic antibody–associated vasculitis - Weiwei Hao; Qianqian Liu; Xiaoping Li; Yiran Xu; Wenjuan Guan; Lei Zhang; Fang Dong; Wenjun Cao; Shengyun Liu; Wei Li (Arthritis Research & Therapy)
Abstract Objective The present cohort study aimed to evaluate the value of CCL23 in diagnosis, disease activity, and prognosis in patients with antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Methods CCL23 levels in serum samples from 317 patients with AAV and 83 healthy controls (HCs) were measured using a customized immune response kit. Results Patients with AAV had significantly elevated CL23 levels compared with HCs. CCL23 level was closely related to disease activity and was better than birmingham vasculitis activity score (BVAS) in distinguishing disease relapse from remission (area under curve: CCL23 = 0.942, BVAS = 0.84). Elevated CCL23 level was associated with poor prognosis within a 1 year follow-up period in patients with AAV (p = 0.0001). The ability of CCL23 to predict the poor prognosis of disease is better than that of five-factor score. Furthermore, elevated CCL23 levels were a risk factor for renal involvement (odds ratio = 1.722, p = 0.033), and were significantly related to serum creatinine (r = 0.381, p = 0.009) and eGFR (r = − 0.382, p = 0.01) at the time of diagnosis. High CCL23 level at diagnosis was associated with increased adverse outcomes during 1 year follow-up in patients with AAV with renal involvement (p = 0.0242). Conclusion Elevated serum CCL23 level was closely related with disease activity and renal involvement in patients with AAV, can be a potential biomarker for diagnosis, and can predict prognosis in patients with AAV, especially adverse renal prognosis.